THE CASE OF IMMIGRANT PARENTS IN RAISING THEIR MULTILINGUAL CHILDREN - Ersika Puspita Dani; Friska Yanti Simaremare (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2020)
This qualitative research investigated real events in the case of immigrant parents in raising their multilingual children. This focused to find out what kinds of the parenting style to make their children multilingual, how the processes occurred, and what the language problems during the multilingual children process were. In conducting this research, natural social phenomenon methods in interview transcript, field notes, visual materials, photographs, video recordings, documented human experiences whose data were collected and analyzed. There were three findings, they were (1) there are two styles of parenting applied by 8 parents, involves: 7 parents applied the authoritative parenting styles, and 1 parents applied authoritarian style in raising their multilingual children. (2) There are many processes that are done by parents in raising their multilingual children. Dominantly, multilingual children have used to learn multilingual languages from their parents and environments, their parents always familiarize themselves to always be able to adjust in social, cultural, habits, geographical residence, and so on, which is always supported by the situations, and conditions occurred at that time. (3) There are only two kids are found to have a problem, namely dyslexia and code switching.